2005
DOI: 10.1088/0965-0393/13/3/012
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional numerical simulation of weld solidification cracking

Abstract: It is difficult to measure mechanical strain in the vicinity of a moving weld pool owing to the complex solidification process. Computational modelling of the welding process provides an effective method to study the stress/strain distributions of the weldment. In this paper, the driving force to weld solidification cracking, i.e. mechanical strain versus temperature at the trail of a weld molten pool, was modelled with the three-dimensional finite element analysis procedure. The dynamic stress/strain evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Modeling these effects and their impact on solidification crack formation remains a difficult subject. Therefore, only multi-scale, multi-physics models, as the ones used to investigate weldability and solidification cracking behavior [85][86][87][88][89][90][91][92][93][94][95][96][97][98] [99,100], can efficiently simulate welding speed effect on solidification crack formation. Complex simulations to describe the travel speed effect must include modeling both microstructure and thermo-mechanical cells with the implementation of solidification cracking criteria.…”
Section: E Simulating Travel Speed Effectmentioning
confidence: 99%
“…Modeling these effects and their impact on solidification crack formation remains a difficult subject. Therefore, only multi-scale, multi-physics models, as the ones used to investigate weldability and solidification cracking behavior [85][86][87][88][89][90][91][92][93][94][95][96][97][98] [99,100], can efficiently simulate welding speed effect on solidification crack formation. Complex simulations to describe the travel speed effect must include modeling both microstructure and thermo-mechanical cells with the implementation of solidification cracking criteria.…”
Section: E Simulating Travel Speed Effectmentioning
confidence: 99%
“…Up to date, parameters such as mechanical strain, 22,24,25,35 plastic strain 23 and plastic strain rate 26,27 have been used to analyse the crack initiation. In this study, the mechanical strain was adopted to analyse the solidification cracking behaviour.…”
Section: Evolution Of Mechanical Strain During Weldingmentioning
confidence: 99%
“…When the material is liquid, the related rigidity and resistance are negligible, but both yielding strength and Young modulus were not considered to be nil in order to reduce computation times, but they were limited to small values (5 MPa and 0.1 GPa respectively) around which any deviation does not modify the mechanical results. Similarly, as commonly used and justified elsewhere, the related thermal expansion coefficient was considered very small in order to avoid computation divergence (Taleb et al, 2004;Wei et al, 2005;Taljat et al, 1998). Furthermore, after incorporating a viscous contribution in the constitutive law representing the alloy behavior at high temperature, comparisons between computed and experimental results showed that the lower the viscous contribution, the smaller the deviations are.…”
Section: Mechanical and Metallurgical Modelingmentioning
confidence: 99%